Predictive effects of managerial need support, basic psychological need satisfaction, and role overload on work engagement - Yap, Chui Yan (2010)
The main objective of this study is to examine whether or not the relationship between managerial need support and work engagement is mediated by basic psychological need satisfaction and moderated by role overload. Specifically, by drawing on selfdetermination theory, role stress theory, and substitutes for leadership theory, this study hypothesizes that (a) managerial need support is positively related to work engagement; (b) the relationship between managerial need support and work engagement is mediated partially by basic psychological need satisfaction; (c) role overload moderates the indirect and direct effects of managerial need support on work engagement; and (d) role overload is negatively related to basic psychological need satisfaction. In order to test these hypothesized relationships, statistical procedures that combine mediation and moderation were used to analyze the survey data collected from 348 full-time employees working in four organizations in Malaysia. The results of this study showed that managerial need support predicted work engagement directly and indirectly through basic psychological need satisfaction. The results also indicated that role overload moderated the (a) relationship between managerial need support and basic psychological need satisfaction (i.e., first stage moderation) and (b) direct relationship between managerial need support and work engagement (i.e., direct effect moderation). As expected, the effect of managerial need support on basic psychological need satisfaction and work engagement was weaker when role overload was high than when role overload was low. Contrary to expectations, the results showed that there was no significant negative relationship between role overload and basic psychological need satisfaction. With regard to theoretical contributions, this study addresses the existing gaps in the work engagement literature by (a) developing and testing a more complete model of work engagement that combines mediation and moderation, (b) bringing in new theoretical perspectives for research on work engagement, and (c) exploring a new predictor, mediator, and moderator in the work engagement literature. With regard to practical implications, employers interested in developing an engaged workforce may want to ()./ensure that managers are trained to be more need-supportive, (b) design jobs and provide a work environment that satisfy employees' basic psychological needs, and () pay close attention to early signs of role overload among their employees. Given the power of a fully engaged workforce for improving organizational performance, continued efforts to identify other potential predictors of work engagement will be worth pursuing.